Mapping IoT-Based Sociocultural Research Trends Over the Last Six Years: Bibliometric Analysis - Hobir, Abdul; Yunanto, Fredy; Jumesam, Jumesam; Vikki Ariyanto, Sandy; Vivekanantharasa, Raveenthiran; Ariwidodo, Eko (KARSA Journal of Social and Islamic Culture, 2024)
This research aims to examine scientific progress and provide a comprehensive literature review regarding IoT-based sociocultural from 2018 to 2023 using the Scopus database. Additionally, this research aims to identify new concepts and areas of limited knowledge that may require additional investigation. Software from the Scopus website was used for bibliometric analysis. Several citations are used to categorize research findings, which also contain information on author, country, document type, and year of publication. The researchers found eighteen papers by limiting their search to the last six years and using only English keywords. 2021 tops the list of years with the most publications, with five documents. Usually, this category of documents is encountered at international paper conferences. According to this analysis, the number of studies related to IoT-based sociocultural issues in the Scopus database is expected to increase and climax between 2018 and 2023. Various themes and keywords that can form the basis for further investigation have emerged with advances in IoT-based sociocultural research. Future academics will be able to analyze IoT-based sociocultural al changes over the past decades with the help of this bibliographic analysis. To equip ourselves to face future questions, bibliometric analysis provides insights and data related to the progress of sociocultural al research based on the Internet of Things.